Novel Epigenetic Clock Biomarkers of Age-Related Macular Degeneration - Mallik, Saurav; Grodstein, Fran; Bennett, David A.; Vavvas, Demetrios G.; Lemos, Bernardo (Frontiers in Medicine, 2022)
Age-Related Macular Degeneration (AMD) leads to the progressive loss of photoreceptors. Loss occurs specially in the macular region (the central part) of the retina and results in irreversible vision impairment. Regression age clocks (models) are one of the most promising aging biomarkers. Here, we provided an extensive analysis to identify regression age clocks for the retina and explored their use in AMD using transcriptomic data. The clocks yielded good separation among AMD samples with increasing severity score (MGS1-4), regardless of whether clocks were trained in retina samples, dermal fibroblasts, or in combined datasets. Clock applications to stem cells and iPSC cells confirm the expected model behaviour with age reprograming in iPSCs. Model application to in vitro neuronal differentiation suggests broader applications. Interesting, many of the age clock genes identified include known targets mechanistically linked to AMD and aging, such as GDF11, C16ORF72, and FBN2. This study provides new observations for retina age clocks and suggest new applications for monitoring in vitro neuronal differentiation. The clocks provide markers for AMD as well as promising targets for in vitro screens and intervention.